End of life in patients attended by pediatric palliative care teams: what factors influence the place of death and compliance with family preferences? - Peláez-Cantero, María José; Morales-Asencio, José Miguel; Navarro-Mingorance, Álvaro; Madrid-Rodríguez, Aurora; Tavera-Tolmo, Ángela; Escobosa-Sánchez, Olga María; Martino-Alba, Ricardo (Springer, 2023)
Each year, more than 8 million children worldwide require specialized palliative care, yet there is little evidence available in pediatrics on the characteristics of the end of life in this context. Our aim is to analyze the characteristics of patients who die in the care of specific pediatric palliative care teams. This is ambispective, analytical observational, multicenter study conducted between 1 January and 31 December 2019. Fourteen specific pediatric palliative care teams participated. There are 164 patients, most of them suffering from oncologic, neurologic, and neuromuscular processes. The follow-up time was 2.4 months. The parents voiced preferences in respect of the place of death for 125 of the patients (76.2%). The place of death for 95 patients (57.9%) was at the hospital and 67 (40.9%) was at home. The existence of a palliative care team for over 5 years is more likely to be related to families voicing preferences and their fulfillment. Longer follow-up times by pediatric palliative care teams were observed in families with whom preferences regarding the place of death were discussed and in patients who died at home. Patients who did not receive home visits, when the pediatric palliative care team did not provide full care and when preferences regarding the place of death were not discussed with parents, were more likely to die in the hospital. Conclusions: Advance planning of end-of-life care is one of the most important aspects of pediatric palliative care. The provision of services by the teams and the follow-up time are related to parents’ expressed preferences and the place of death.
Keywords: Niños - Enfermedades - Tratamiento paliativo; Pediatría; Cuidados terminales; Advance directives; Child mortality; Decision-making; Infant death palliative care; Right to die; Terminal care